Performance of Rapid Immunochromatographic Test on Malaria Infecton Among Expectant Women in Kericho County, Kenya - Annastasia Njeru; Joshua Mutiso; Albert Kimutai; Erick K. Mibei (European Scientific Journal, ESJ, 2019)
Background: Microscopy is the gold standard method currently acceptable in diagnosis of malaria in a clinical setting but is subject to diagnostic bias as it cannot detect malaria parasites as they are very low or absent in peripheral circulation. Rapid immunochromatographic test (ICT) can detect the parasite antigen in peripheraral circulation and thus may be a suitable complementary epidemiological tool for malaria diagnosis among the expectant women in low parasitaemia areas. However, the sensitivity and accuracy of rapid ICT in diagnosis of malaria in pregnancy has not been established. Methods: A laboratory based cross sectional study was used. Blood samples from 314 pregnant women attending the antenatal clinic were screened for malaria parasites using microscopy, rapid ICT and polymerase chain reaction (PCR). Results: Out of the 314 samples analyzed for malaria, 44 samples (14.0%) were positive for P. falciparum by microscopy while 62 (19.7%) were positive by rapid ICT. The sensitivity and specificity of rapid ICT was 84.4% and 96.8% respectively while that of microscopy was 68.8% and 100.0% respectively. There was a moderate level of agreement between results of rapid ICT and microscopy and high level of agreement when rapid ICT results were compared against microscopy and PCR results (κ = 0.517; p <0.001 and κ = 0.821; p <0.001) respectively. Conclusion:The findings of this study suggest the potential adoption of rapid ICT as a complementary epidemiology tool for malaria diagnosis among expectant women in areas of low parasitaemia and where microscopy is difficult to implement.